Pengaruh Media Crossword Puzzle dalam Meningkatkan Maharah Qira’ah Siswa SMA Islam Sabilillah Malang Boarding School - Apri Wardana Ritonga (Universitas Yudharta Pasuruan, 2020)
Maharah qira'ah is one of the Arabic language skills that students must have. Teaching maharah qira'ah should be done in a variety of interesting media so that learning becomes fun and enjoyable. Crossword puzzles are an option that can be used as a medium in teaching maharah qira'ah to students. This study aims to determine the effect of the crossword puzzle media in learning maharah qira'ah. The experimental method with the form of pre-experimental research design is the method used in this study. The population that became the object of the study was 125 students of class XII SMA Islam Sabilillah Malang Boarding School consisting of 5 classes, two female classes and three male classes. Based on the results of data analysis, the pre-test mean score was 79.83 (80), and the post-test average score was 85.43 (85). With the results of the analysis of tcount 91.539 and ttable 2.001, it means that tcount ˃ ttable. So Ho is rejected and Ha is accepted with a significance level of 0.2%. So, it can be concluded that there is an effect of using crossword puzzle media in improving maharah qira'ah for XII grade students of SMA Islam Sabilillah Malang Boarding School.